Crafting Democracy : How Novgorod Has Coped with Rapid Social Change - Petro, Nicolai N. (Book collections on Project MUSE., 2004)
The Novgorod region of Russia is a sparsely populated area about the size of Ireland better known for its medieval archaeology and folklore than for anything else. Although Novgorod began the post-Soviet period with no unusual endowment of natural or human resources, it has attracted a large amount of foreign investment. Its dramatic economic success and political innovation have impressed observers. Local governments deliver benefits and services reliably, and the regional government responds quickly to citizens' needs and demands. Something noteworthy is happening in Novgorod that does not square with familiar headlines about contemporary Russia: oligarchs and oil, ethnic tensions and corruption. Nicolai N. Petro attempts to explain the Novgorod phenomenon by seeking answers at the regional level. Novgorod is, he finds, a model of effective democratic consolidation. Petro suggests that the region owes its unexpected recent success to its political elites, who have identified key cultural symbols and used those symbols to promote democratic development. Drawing on comparisons with other regions and countries, Petro finds that these cultural tactics often yield better results than do Western-style institutions and educational training programs. "Current efforts to promote democracy focus too much on structural changes and not enough on the conditions needed to sustain them," Petro writes. "For the rule of law, free markets, and free and fair elections to gain broad public support, they must first make sense within the local cultural tradition." The unexpected success of regional democratic development in a country not known for its democratic traditions suggests that local governments can transform the burden of the past into an ally of change, a finding with implications for democratic development initiatives in other areas of the world